The mysterious beauty of 6174 / Siti Mariam Saad - Saad, Siti Mariam (Unit Penerbitan Dan Publisiti JSKM, 2023)
The mysterious number 6174 is known as the Kaprekar’s constant. It was discovered by Indian mathematician D. R. Kaprekar in 1949. What makes this number so mysterious?